Wine and wine tourism experience: a theoretical and conceptual review - Santos, Vasco (2019)
Purpose – This paper aims to provide a theoretical and conceptual analysis of wine and wine tourism experiences evidencing the current state of the art and providing some directions for future research. Design/methodology/approach – The paper provides an in-depth literature review and content analysis of prior work. Findings – The experience focussed on wine and wine tourism requires further exploration. The boundaries of the wine and wine tourism experience were identified, together with highlights and strategic agenda for future actions. Originality/value – Based on some key prior literature on the topic of wine and tourism experience, future research directions and approaches were proposed.